(untitled) (International Journal of Engineering and Computer Science, 2017)
Memory management is basic for all languages because it is the important factor to determine the efficiency of the language. Language like Java have own garbage collector hence the programmer no need to do memory management. But in C++ the programmer has to release the memory through new and delete functions. In this paper, we are going to discuss how the memory is managed in both the languages and what are all the issues are there in memory in both the languages.